A new robot skin for force and position detection. Issue 6 (20th October 2014) - Wu, Haibin; Su, Yixian; Shi, Jinjin; Li, Jinwen; Ye, Jinhua
Abstract : Purpose: – The aim of the research is to achieve a robot skin which is easy to use, and can detect both position and force interacted between robot and environments. Design/methodology/approach: – The new type of robot skin proposed in this paper includes two functional modules – contact position sensor and contact force sensor. The contact position sensor module is based on the resistor divider principle, which consists of two perpendicular conductive fiber layers and insulated dot spacer between them. The contact force sensor module is based on capacitance change theory, which consists of two soft conductive plates and a viscoelastic layer between them. By combining the two modules, the soft robot skin was designed. Findings: – Simulation and experiment results demonstrate that the proposed robot skin design is feasible and effective enough to sense contact position and contact force simultaneously. Practical implications: – This robot skin is low-cost and easy to make and use, which provides safety solutions for most of the robot. Originality/value: – For the first time, an integrated robot skin which can get contact position and force information simultaneously is designed. Unlike general tactile sensor matrices, this robot skin has only six leads. Furthermore, the number of leads does not increase with the enlarging of sensor area. Soft and simple structure of the robot skin makes it possible to cover any region of the robot body.